The weird: a dis/orientation. Issue 6 (19th September 2017) - Luckhurst, Roger
ABSTRACT: This essay attempts to explore the recent resurgence of interest in 'weird fiction' from Arthur Machen in the 1890s via H. P. Lovecraft in the 1920s to the rise of the New Weird in 2003 and beyond in the works of China Miéville, M. John Harrison and Jeff VanderMeer. It aims to provide an overview of its slippery genre status, existing as it does in the interstices of gothic and science fiction, decadent and pulp fiction. But it also recognizes that the very slipperiness of the genre insidiously undermines any fixity of definition, constantly shifting boundaries and defying the act of ever being fully 'introduced'. An orientation in this emergent field is also about acknowledging disorientation.